2014
DOI: 10.3748/wjg.v20.i48.18390
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of tumor necrosis factor-α is associated with advanced colorectal cancer stages

Abstract: METHODS:Archival tissue specimens were collected from 30 patients with CRC who had undergone surgical intervention at King Khalid University Hospital. Patient demographic information, including age and gender, tumor sites, and histological type of CRC, was recorded. To measure TNF-a mRNA expression in CRC, total RNA was extracted from tumor formalin-fixed, paraffinembedded, and adjacent normal tissues. Reverse transcription and reverse transcription polymerase chain reaction were performed. Colorectal tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 36 publications
9
78
0
Order By: Relevance
“…We investigated the concentration of these cytokines in lysates of CRC and paired normal tissue and found a statistically significantly higher concentration in cancer tissue. These findings are consistent with data from previous studies (33)(34)(35). Interestingly, we also noted a statistically significantly positively correlation between the level of IL32 and these cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…We investigated the concentration of these cytokines in lysates of CRC and paired normal tissue and found a statistically significantly higher concentration in cancer tissue. These findings are consistent with data from previous studies (33)(34)(35). Interestingly, we also noted a statistically significantly positively correlation between the level of IL32 and these cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…TNF has been associated with a wide range of biological activities, including inflammation and cell differentiation (Sedger and McDermott, 2014). Studies have demonstrated that over expression of TNF in CRC can be associated with tumor progression, invasion, and metastasis (Al Obeed et al, 2014). Thus, aberrant Ecadherin and TNF gene expression is consistent with the increased tumor invasiveness observed in our study in the group fed hemin + I3C.…”
Section: Discussionsupporting
confidence: 82%
“…Administration of DMH induced colon cancer in rats exhibited significant increase in TNF-alpha colon tissues (Table2). The relative expression of TNF-α mRNA in colorectal cancer was significantly higher than that present in adjacent normal colorectal tissue (Al Obeed et al, 2014).Due to metabolism of DMH, the production of excess ROS ends in the activation of TNF-α by p65-NF-ĸB pathway. Enhanced level of TNF-α could damage function and transcription of the affected proteins and progression of epithelial cell transformation to invasive cancer in colonic mucosa through initiating the inflammation and progression of cancer (Anna et al, 2015 andGarza-Trevino et al, 2015).…”
Section: Discussionmentioning
confidence: 89%